3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:44:37
3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)3
3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)
3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)
3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)
3xy(x²-xy²+xy)-xy²(2x²-xy+2x)
=3x³y-3x²y³+3x²y²-2x³y²+x²y²-2x²y²
=3x³y-2x³y²-3x²y³+2x²y² (求值)
如果是因式分解:
3xy(x²-xy²+xy)-xy²(2x²-xy+2x)
=3x³y-3x²y³+3x²y²-2x³y²+x²y²-2x²y²
=3x³y-2x³y²-3x²y³+2x²y²
=3xy(x²-y²)-2x²y²(x-1)
=xy[(3(x²-y²)-2xy(x-1)]
=xy(3x²-2x²y-3y²+2xy)
(-3xy+2xy)-(4xy+xy)
3xy(x^2-xy^2+xy)-xy^2(2x^2-xy+2x)
3xy-3xy-xy+2yx
3xy-4xy-(-2xy)
3xy-4xy-(-2xy)
2xy.(-3xy)÷(xy)
2xy-xy-(-3xy)=
2x²y-3(2xy-xy)-xy
因式分解X^3-2xy+xy^2
[(2xy-3)(2xy+3)+(xy+3)^2]/(-xy)
xy-3xy+2xy-xy
3xy^2*(-2xy)
化简:xy分之3x^2+2xy-xy分之2x^2-xy=
3xy(x^2y-xy^2+xy)-xy^2(2x^2-6xy+2x)过程
计算:3xy(x²y-xy²+xy)-xy²(2x-xy+2x)
xy-2{xy-[3x^2y-(4xy^2+0.5xy)]+4x^2y}+6xy^2
(X-3xy+4xy-y)-[-2x-2(xy-3/2xy)-y]+6xy的过程
xy